The Relationship between FOMO and Work Motivation with Employee Performance in Gen Z - Fitria, Novy (Jurnal Ilmu Manajemen Advantage, 2023)
The purpose of this research is to see the relationship between FOMO and motivation and employee performance in Gen Z. This research uses quantitative methods by collecting data using questionnaires in Gen Z with purposive sampling techniques. The research data obtained was analyzed using multiple regression analysis. Based on the results of the F test, F= 5.156 with p= 0.007 (p<0.05) means there is a significant relationship between FOMO and motivation and performance. These findings indicate that the hypothesis which states that there is a relationship between FOMO and motivation and employee performance in Gen Z is accepted/proven. The results of the partial analysis show that between FOMO and performance, t= -0.211 with Sig. 0.008 (p<0.05) means that there is a significant negative relationship between FOMO and proven performance, meaning that the higher the FOMO in Gen Z, the more their performance will decrease and so does on the contrary. The relationship between motivation and performance was obtained t= 0.175 with Sig.0.018 (0<0.05) meaning there is a significant positive relationship between motivation and performance, the higher the motivation, the higher the performance of Gen Z employees and conversely the lower the motivation of Gen Z, the higher the performance decrease.